Less Market, Equal Family: Welfare and Caregiving in the Ecuador of the Citizens’ Revolution - Analía Minteguiaga; Gemma Ubasart-González (Íconos)
In light of contemporary efforts of some governments in the region to distance themselves from the neoliberal paradigm, this article aims to study the politics of welfare and care implemented by the Rafael Correa government. Turning to the literature on welfare regimes, this article tries to capture the existence of continuities and/or breaks in the politics of social intervention with respect to the liberalization period, and their effects on the production of welfare. As a result, this study makes reference to the configuration of a regime that displays a remarkable decommodification process, however weakened by its defamilization in the production of social welfare.